Taufe und Recht einige einführende Bemerkungen - Meyer, Christoph H. F. 1966- (2013)
This article deals with a particular aspect of the relation between baptism and law in the early middle ages, a topic that has hardly been explored by historical research. The main focus of the paper is on the role of baptism at the beginning of a long development which led to the modern notion that every human being as a natural person is a subject of rights and obligations. The article approaches ist subject from two different directions. First, on a theoretical and abstract level it raises the question to what extent there were points of departure towards the concept of a person in medieval Christian thinking. From this perspective inter alia two phenomena come into view: the character (indelebilis) as the basis for an inalienable status as a Christian and the role the soul as well as salvation played in law. The second part of this paper consists of particular historical evidence. After some brief observations as regards the relation between Roman citizenship and Christian baptism in late Antiquity the article focuses on the legal status of the newborn infant in the secular law of the early Middle Ages. In this context one has to distinguish between a pre-Christian >barbarian< legal tradition and norms of later Christian origin. In both traditions formal acts like the acceptance of the child and baptism played a major role. However, there are also differences which indicate general changes in the comprehension of what constitutes a human being from a legal point of view.
Keywords: Taufe; Recht; Geschichte; Mittelalter; Sakramentenrecht; Europa; Amerika